Reformasi Konsep Heat of Passion: Menuju Pembatasan Provokasi dalam Mengurangi Pertanggungjawaban Pidana Pembunuhan - Kadir, Zul Khaidir (JUSTITIABLE - Jurnal Hukum, 2025)
The concept of heat of passion in criminal law has developed as a form of recognition of extreme emotional conditions that can reduce the criminal responsibility of the perpetrator, especially in cases of murder. Although this doctrine is historically rooted in the common law system and has been adopted in various legal systems, its relevance in the modern legal context is debatable. Changes in social values, technological advances, and demands for legal certainty and substantive justice challenge the validity of the application of heat of passion as a partial defense. This study aims to review the validity and normative structure of heat of passion, emphasizing the need for reformulation of the elements of provocation and loss of control to be more adaptive to the contemporary context. This study uses normative research using a comparative approach. The results of the study indicate that ambiguity of definition, inconsistency of application, and gender bias are the main weaknesses in the application of this doctrine. Therefore, a new evaluative framework is needed that is more objective, inclusive, and based on restorative justice. This reformulation is expected to ensure that criminal law remains relevant in providing protection for victims, enforcing individual accountability, and reflecting progressive values ​​in a modern legal society.